Modification and Processing of Biodegradable Polymers - Moraczewski, Krzysztof (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Polymeric products made from petrochemical polymers are extremely stable in environmental conditions. After their exploitation, this becomes a serious problem for the environment. Most of the products made of plastic are stockpiled in landfills, and the decomposition time of such products is often several hundred years. The solution to this problem may be the use of biodegradable polymers derived from renewable materials, undergoing a process of biodegradation.Biodegradable polymers are distinctly different than regular polymers in material characteristics. Biodegradable polymers like any other polymer can be processed using conventional techniques such as injection molding, extrusion, and compression molding. Furthermore using appropriate methods of modification, new or improved properties of materials can be obtained. However, the distinct narrow modification and processing window makes them a challenge to modify or process.Continuing technological progress in the modification and processing of biodegradable polymers leads not only to the enhancement of the product quality, but also to the reduction of their prices. As a result, biodebradable polymers may be used to produce both common-use articles or packaging materials, as well as more complex engineering applications.In this reprint, we aimed therefore to publish original work and reviews about the current trends and technologies for the modification and processing of biodegradable polymers and its composites aimed at improving their properties and extending the application possibilities.